Respuesta :

For this translation, you need to replace every occurrence of "x" with "x-3", and every occurrence of "y" with "y+5".

Answer:

[tex](x,y)\rightarrow (x+3,y-5)[/tex]

Step-by-step explanation:

In translation by a unit left,

The rule is,

[tex](x,y)\rightarrow (x-a,y)[/tex]

By a unit Right, rule is,

[tex](x,y)\rightarrow (x+a,y)[/tex]

By a unit up rule is,

[tex](x,y)\rightarrow (x,y+a)[/tex]

By a unit down, rule is,

[tex](x,y)\rightarrow (x,y-a)[/tex]

Hence, the rule describes a translation that is 3 units to the right and 5 units down is,

[tex](x,y)\rightarrow (x+3,y-5)[/tex]